A comparative study of different surgical methods in the treatment of traumatic temporomandibular joint ankylosis. Issue 2 (February 2017) - Xu, F.; Jiang, L.; Man, C.
Abstract: Two different surgical methods for the treatment of unilateral traumatic temporomandibular joint (TMJ) ankylosis with a medially displaced residual condyle are described. Eighteen patients with unilateral traumatic TMJ ankylosis and a medially displaced residual condyle, treated between 2008 and 2013, were included in this study. Group A patients ( n  = 10) were treated with an autogenous coronoid process graft (ACPG) for reconstruction of the mandibular condyle, while group B patients ( n  = 8) were treated by lateral arthroplasty (LAP); a temporalis myofascial flap (TMF) was used as interpositional material in both groups. The long-term results of the two treatments were compared through postoperative computed tomography and clinical follow-up examinations. The two groups were compared in terms of the recurrence rate, facial pattern change, and improvement in maximum inter-incisal opening (MIO) using SPSS 18.0 software. All patients were followed up for 12–24 months. Two patients in group A (20%) had reankylosis; no reankylosis was observed in group B patients. Compared with the ACPG, LAP improved the facial pattern and MIO significantly ( P  < 0.05). LAP is a feasible and effective surgical method for the treatment of unilateral traumatic TMJ ankylosis when the displaced residual condyle is bigger than one third of the condylar head.